2013
DOI: 10.1002/cphc.201201006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopy, and Computational Analysis of Photoluminescent Bis(aminophenyl)‐Substituted Thiophene Derivatives

Abstract: Substituted oligothiophenes have a long history in the field of organic electronics, as they often combine outstanding electro-optical properties with the ease of synthesis. To assist the rational selection of the most promising structures to be synthesized, there is the demand for tools that allow prediction of the properties of the materials. In this study, we present strategies for synthesis and computational characterization, with respect to the fluorescence behavior of oligothiophene-based materials for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 64 publications
3
25
0
Order By: Relevance
“…Previously, we used B3P86 and B3LYP hybrid functionals to predict the maximum absorption bands of a series of natural polyphenols [27]. Lumpi et al (2013) showed that the M06-2X hybrid functional was suitable to predict the absorption and emission spectra of oligothiophene-based compounds [28]. Quartarolo and Russo applied PBE0 and ab initio multi-reference coupled cluster with the resolution of identity approximation (RICC2) approaches to predict the UV-Visible spectra of pyranoanthocyanins, a class of derived anthocyanin molecules; they showed that the use of larger basis sets results in little improvement of excitation energies, and that the conformational effect has a slight influence on the λMAX predictions [29].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we used B3P86 and B3LYP hybrid functionals to predict the maximum absorption bands of a series of natural polyphenols [27]. Lumpi et al (2013) showed that the M06-2X hybrid functional was suitable to predict the absorption and emission spectra of oligothiophene-based compounds [28]. Quartarolo and Russo applied PBE0 and ab initio multi-reference coupled cluster with the resolution of identity approximation (RICC2) approaches to predict the UV-Visible spectra of pyranoanthocyanins, a class of derived anthocyanin molecules; they showed that the use of larger basis sets results in little improvement of excitation energies, and that the conformational effect has a slight influence on the λMAX predictions [29].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical computations have improved our understanding of organic electronic devices considerably by giving a first-principles description of electronically excited states [1][2][3][4][5][6]. These methods provide accurate estimates of excitation energies and molecular properties and give detailed insight into the state character through the molecular orbitals (MOs) involved.…”
Section: Introductionmentioning
confidence: 99%
“…In solid-state physics the same problem appears in a different way: the inability of standard TDDFT to describe excitonic effects and the ensuing bound electron-hole pair [15,22,33]. For large molecular systems one may expect that this latter issue comes into play and there is indeed increasing evidence [33][34][35][36][37][38][39] that the resulting dynamic electron-hole separation has a similarly detrimental effect on TDDFT as directed charge transfer does. In spite of the fact that a number of diagnostics have been developed with the aim of quantifying charge separation [40][41][42][43][44] no general solution exists yet and TDDFT is still described to suffer from "significant but hard-to-detect errors" [37].…”
Section: Introductionmentioning
confidence: 99%
“…Geometries, frontier orbitals and total energies of ground state (S 0 ) and first excited state (S 1 ) of p6P and 6T were obtained using DFT. We make use of two different DFT functionals: i) the M06-2X functional, [1,2] which has proven to properly describe the spectroscopic properties of these type of systems [2,3] and ii) the CAM-B3YP functional, that has a good track record in the description of the electronic processes in organic molecules. [4,5] Artigo Geral 64…”
Section: Methodsmentioning
confidence: 99%